Cooperation : an experimental analysis - Marwell, Gerald, 1937-; Schmitt, David R. (Academic Press, 1975)
Cooperation: An Experimental Analysis presents the results of an experimental analysis that sought to identify the factors that inhibit, maintain, or promote cooperation. Two of these factors are given particular attention: inequity and interpersonal risk between potential cooperators. Using a molar approach, the book applies some of the key methodological and theoretical insights of behavioral analysis to a group response that reflects the main conceptual characteristics of cooperation. The extent to which this behavioral response could be controlled by relevant environmental contingencies is also examined. Comprised of nine chapters, this book begins with an overview of the concept of cooperation and the measurement and experimental design used in the study. It then summarizes the results of the first experiments that focus on the link between inequity and cooperation, followed by a discussion on the effect of interpersonal risk on cooperation. Subsequent chapters focus on the role of protection and communication in promoting cooperation despite the presence of risk; the effects of the relationships between partners on the likelihood of cooperating under risk; and how a strategy of "pacifism" could facilitate cooperation. The final chapter summarizes the results of the experiments. This monograph will be of interest to social psychologists and sociologists.